Assessment of Safety, Immunogenicity and Preventive Efficacy of Prevenar-13 in Children with Bronchopulmonary Dysplasia - E. S. Zubova; V. V. Semerikov; L. V. Sofronova; M. P. Kostinov (Эпидемиология и вакцинопрофилактика)
Relevance. Bronchopulmonary dysplasia (BPD) is the most frequent chronic pathology of the lungs in children of the first year of life, especially among children born with extremely low and very low  birth weight.Goal. The safety, immunogenicity and preventive efficacy of Prevenar 13 in preterm infants with bronchopulmonary dysplasia were assessedMaterials and methods. There were 29 children under observation, as well as 29 non-vaccinated children as a comparison group. Oxygen support was not needed by any child with BPD. Children in both groups had consequences of perinatal involvement of the central nervous system. Prevenar 13 vaccine was used for immunization.Results. The level vaccine adverse event following immunization in the group of vaccinated children was 16.7 ± 0.07%. One child had a  high body temperature up to 39.5 °C, it was required to prescribe  antipyretic drugs in the age-related dosage. All vaccine adverse event following immunization disappeared on 2 day. Local reactions were not recorded.Conclusions. The use of the Prevenar13 vaccine has established high preventive efficacy among preterm infants with BPD, a decrease in the incidence of otitis media by 3.5 times. Evaluation of  the immunogenicity of the Prevenar 13 vaccine among children with  BPD showed good immunological efficacy (a 4-fold increase in the mean geometric titer of antibodies at 28 days after vaccination).